Zastosowanie platformy e-procurement w działalności operatora pocztowego - Drab-Kurowska, Anna (Using of E-Procurement Platform in Postal Operator Activity, 2005)
Article presents basic directions of changes in area of working of postal operator in Poland. The permanently evolving marked caused an increase of interest in new solutions in the sphere of logistic system. Moreover the importance of the problematic of e-procurement is firmly underlined by the growing costs. Therefore building an efficient e-procurement system should become a priority for Polish Post.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 151-157